Pemanfaatan Media Komputer Dalam Pembelajaran Bahasa Inggris Dengan Metode Direct Method (Internet Based) - Sulistyawati, Meiva Eka Sri; Dewi, Nurmala; Andayani, Endang Sri (JURIKOM (Jurnal Riset Komputer), 2019)
In the era of advanced technology, the use of computer in many aspects has been the part of our life. Moreover, computer has been used in the field of education. The use of computer in teaching and learning has many benefits, not only for the teachers but also the students. So does with English. It has been a compulsory subject in many levels of education. In fact, there are many methods of teaching English that can be used. Using the direct method, especially internet or other aplications by computer or android, can be one of the creative ways to create an enjoyable and fun atmosphere of teaching and learning English.